2019
DOI: 10.25077/aoj.1.1.38-46.2017
|View full text |Cite
|
Sign up to set email alerts
|

Korelasi Ekspresi Immunositokimia Vascular Endothelial Growth Factor a (Vegf A) Dengan Protein Gene Product 9,5 (Pgp 9,5) Darah Haid Pada Patofisiologi Endometriosis

Abstract: There are changes of eutopic endometrium molecular fenotipe in endometriosis such as changes in gene expression, steroid hormone response, increase of inflammation marker and cellular adhesion molecule, decrease of apoptotic index and decidualization capacity, increase of oxidative stress marker, increase activity of angiogenesis and neurogenesis. This study was conducted to analyze the differences in the expression of angiogenic factors (VEGF A) and neurogenesis factors (PGP 9.5) eutopic endometrium of menstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…5,17,18 Their expression can also be found weakly in some cases of intramuscular myoma. 17,19 In this study, as reported by Zhang and Tokushige, expression of both proteins are found in strong intensity and proved their role in etiopathogenesis of pain in adenomyosis.…”
Section: Discussionsupporting
confidence: 77%
“…5,17,18 Their expression can also be found weakly in some cases of intramuscular myoma. 17,19 In this study, as reported by Zhang and Tokushige, expression of both proteins are found in strong intensity and proved their role in etiopathogenesis of pain in adenomyosis.…”
Section: Discussionsupporting
confidence: 77%